Testing the Effects of Seacoast Atmosphere on Tantalum Capacitors - Johanna Virkki; Pasi Raumonen (Active and Passive Electronic Components)
The goal of this research was to test the effects of seacoast atmosphere on tantalum capacitors. Four tests were chosen for this purpose: the 85/85 test was chosen for testing the effects of the combination of high humidity and high temperature, salt spray testing was done for examining the effects of high humidity and salt, temperature cycling test was applied for testing the effects of temperature changes, and a 100% RH humidity test was developed for examining the effects of very high humidity. The results show that combination of high humidity and high temperature did not possess a significant risk for these capacitors during their normal use. Very high humidity and radical temperature changes both affected the breakdown voltages of tantalum capacitors. Salt fog caused corrosion of these components and had a small effect on breakdown voltage but did not have an effect on capacitance or ESR.